Direct and Indirect Effects of Subjective Financial Knowledge with Financial Satisfaction - Jibin Antony; Antony Thomas (Journal of Financial Therapy, 2023)
In this study, we differentiate subjective financial knowledge from objective financial knowledge and propose that subjective financial knowledge relates to financial satisfaction both directly as well as indirectly through financial behavior. This study used data obtained from a multi-stage random sample of household financial officers in Kerala, India (n=450). Results showed that subjective financial knowledge significantly relates to household financial officers’ financial satisfaction after controlling for objective financial knowledge and other socioeconomic factors. The relationship between subjective financial knowledge and financial satisfaction could be both direct and indirect through financial behavior. The findings suggest that financial education programs should focus on enhancing not only objective financial knowledge but also subjective financial knowledge for engaging in responsible financial behavior, which in turn relates to financial satisfaction.
Keywords: Subjective financial knowledge; objective financial knowledge; financial behavior; financial satisfaction.